Polymorphisms of DNA repair genes XRCC1 and LIG4 and idiopathic male infertility - Ghasemi, Hadi; Khodadadi, Iraj; Fattahi, Amir; Moghimbeigi, Abbas; Tavilani, Heidar (Systems biology in reproductive medicine, 2017)
Sperm DNA damage is one of the associated factors of idiopathic male infertility and abnormal spermatogenesis. This study was conducted to assess possible association between risk of male infertility with X-ray repair cross complementing group 1 (XRCC1) Arg399Gln (G to A) and DNA ligase 4 (LIG4) Thr9Ile (C to T) gene polymorphisms which are involved in different DNA repair pathways. In this case-control study 191 fertile and 191 infertile men (29-40 years old) were enrolled. The single-nucleotide polymorphism genotypes and alleles of XRCC1 Arg399Gln and LIG4 Thr9Ile were assessed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. There was no significant association between XRCC1 Arg399Gln polymorphism and risk of male infertility. The frequency of LIG4 Thr9Ile genotypes and alleles were statistically different between fertile and infertile men (p<0.001). We found that the CT genotype increased infertility risk more than threefold (OR, 3.12; 95% CI, 1.803-5.407). The LIG4 TT genotype carriers had decreased progressive motile sperm (p<0.05) and increased non-progressive motile sperm (p<0.001) compared with the CC genotype. Moreover, sperm concentration in subjects carrying the CT genotype was lower than that observed in CC carriers (p<0.05). The results revealed that the GG/CT and GA/CT combinations of genotypes increase the risk of infertility 3.5 and fourfold, respectively (p=0.021 and 0.004, respectively). This study demonstrated that there was an association between LIG4 Thr9Ile polymorphism and male infertility and suggests CT genotype as a risk factor for male infertility.